Effect of adding fat to feedlot rations - B.E. Brent; P.A. Phar; L.J. Randle; L.H. Harbers; Dell M. Allen (Kansas Agricultural Experiment Station Research Reports, 1971)
Fat is added to commercial feedlot rations as a concentrated energy source and to reduce dustiness and wear of feed processing machinery. We added fat at varying levels ( 0 to 6% of the ration) to study effects from fat and the influence of a surface-active additive. Two hundred 700-pound steers were allotted to 40 pens of 5 each all fed 135 days on the rations show in Table 12, according to the schedule shown in Table 13.
Keywords: Cattlemen& #x27; s Day; 1971; Report of progress (Kansas State University. Agricultural Experiment Station); 546; Beef; Fat; Feedlot ration; Energy